2022
DOI: 10.3390/nu14122530
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Prevents Nonalcoholic Fatty Liver Disease by Promoting Fatty Acid Oxidation and Energy Expenditure in C57BL/6 Mice Fed a High-Fat Diet

Abstract: There is a consensus that ferulic acid (FA), the most prominent phenolic acid in whole grains, displays a protective effect in non-alcoholic fatty liver disease (NAFLD), though its underlying mechanism not fully elucidated. This study aimed to investigate the protective effect of FA on high-fat diet (HFD)-induced NAFLD in mice and its potential mechanism. C57BL/6 mice were divided into the control diet (CON) group, the HFD group, and the treatment (HFD+FA) group, fed with an HFD and FA (100 mg/kg/day) by oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The murine liver tissue sections were prepared as described in Luo et al ( 20 ). For immunohistochemistry (IHC) staining, the samples were incubated with antibodies against CYP7A1 (1:50 dilution; Solarbio Technology Co., Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The murine liver tissue sections were prepared as described in Luo et al ( 20 ). For immunohistochemistry (IHC) staining, the samples were incubated with antibodies against CYP7A1 (1:50 dilution; Solarbio Technology Co., Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of mouse liver tissue lysate and western blot analysis were as previously described ( 20 ). The difference is that the PVDF membranes were incubated overnight at 4°C with the antibody against CYP7A1 followed by the secondary antibody (Solarbio Technology Co., Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…It was also reported that FA could ameliorate aflatoxin B1-induced duodenal barrier damage in rats [ 142 ]. FA effectively prevents high-fat diet-induced fatty liver disease by activating the PPARα signaling pathway to decrease the accumulation of triacylglycerol in the liver and increase the consumption of energy [ 143 ]. FA acid has a cardioprotective effect induced by severe endoplasmic reticulum stress [ 144 ].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Furthermore, an initial evaluation of ferulic acid's anticancer activity in HepG2 cells demonstrated its role in inhibiting tumor cell proliferation through inducing apoptosis and autophagy . High-fructose-induced hyperuricemia and NAFLD C1q /CTRP3(+)/ACL(-) (Elseweidy et al, 2022) Ferulic acid Cecal ligation and perforation (CLP)-induced and lipopolysaccharide (LPS)-induced ALI GSK-3β/CREB/ NF-κB(-) (Cao et al, 2021) Aflatoxin B1-induced liver damage CYP450(-)/Nrf2/GST(+) (Wang, He, et al, 2021) CCl4-induced hepatic fibrosis TGF-β1/ Smads(-) (Mu et al, 2018) HCHF-induced NASH ROCK/NF-κB(-) (Wei et al, 2021) HFD-induced NAFLD PPARα(+) (Luo et al, 2022) Chlorogenic acid CCl4-induced liver fibrosis and inflammation TLR4/MyD88/NF-κB(-) (Shi et al, 2013) ANIT-induced liver injury STAT3/NF-κB(-) (Tan et al, 2016) CCl4-induced liver injury NLRP3(-)/Nrf2(+) (Shi et al, 2018) HFD-induced NAFLD TLR4(-) (Shi et al, 2021) MCDD diet-induced NAFLD LPS-TLR4-MyD88(-) (Gu et al, 2023) MCD diet-induced NAFLD ECM/HSCs(-) (Miao et al, 2022) HCC cells Hep-G2 and Huh-7 NF-κB(-)/BBC3(+) (Jiang et al, 2021) Gallic acid aHSCs TRADD/RIP3(+) (Chang et al, 2015) HFD-induced NAFLD rats and palmitic acid (PA) and oleic acid (OA)-treated hepatocytes AMPK/ACC/PPARα(-) (J. Fructose-induced NAFLD AMPK/SREBP-1/ ACC/ FASN axis (-) (Lu et al, 2023)…”
Section: Ferulic Acidmentioning
confidence: 99%
“…Additionally, ferulic acid exhibited anti‐inflammatory effects in rats with NASH by inactivating the ROCK/NF‐κB signaling pathway (Wei et al, 2021). A recent study reported that ferulic acid promotes fatty acid oxidation by activating the PPARα signaling pathway in high‐fat‐diet‐induced NAFLD mice (Luo et al, 2022). Furthermore, an initial evaluation of ferulic acid's anticancer activity in HepG2 cells demonstrated its role in inhibiting tumor cell proliferation through inducing apoptosis and autophagy (Wang et al, 2022).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%